Effects of consumption of whole grain foods rich in lignans in healthy postmenopausal women with moderate serum cholesterol: a pilot study. (August 2014) - Durazzo, A.; Carcea, M.; Adlercreutz, H.; Azzini, E.; Polito, A.; Olivieri, L.; Zaccaria, M.; Meneghini, C.; Maiani, F.; Bausano, G.; Martiri, F.; Samaletdin, A.; et al.
Abstract This study aims at investigating the effect of an experimental period of intake of whole grain foods rich in lignans as part of an habitual diet on the plasma and urinary excretion of enterolignans, the biomarkers of lipid metabolism and the immunological and antioxidant status in a group of postmenopausal women with moderate serum cholesterol. A randomized double-blind crossover study was completed on 13 subjects in 12-weeks after protocol approval of an ethical committee. The subjects consumed whole grain foods high in lignans (30 g/d of breakfast cereals or biscuits, etc., 80 g/d of whole grain pasta) or refined grain foods for 4 weeks, separated by a 2-weeks wash-out period. A modest hypocholesterolemic effect (p < 0.05) of the whole grain diet was observed and the intake of whole grain products rich in lignans was also associated with an increase in urinary enterodiol excretion (p < 0.05).